Pregnancy and contraception in women with Pre-Gestational diabetes in secondary Care– A questionnaire study. (December 2021) - Scott, R.; Oliver, N; Thomas, M.; Agha-Jaffar, R.
Abstract: Aims: To establish the knowledge of women with pre-gestational diabetes about of the risks of diabetes in pregnancy, and investigate their pregnancy plans, contraceptive choices, and preparedness for pregnancy. Methods: Women of reproductive age attending diabetes clinics across a single busy metropolitan NHS Trust were invited to fill in a questionnaire about pregnancy and contraception. The electronic health records of those women were also reviewed. Results: Ninety-six women completed the questionnaire. The majority of respondents (94%) had Type 1 Diabetes. Only 3% of women met the criteria of 'prepared for pregnancy'. Low efficacy contraception was used by 32% of women. Most women were only aware of a few risks to the mother and fetus in pregnancy, though the majority of women were aware of the importance of good glycaemic control before pregnancy. Previous pregnancies, or attendance at pre-conception counselling, did not improve participant knowledge. Conclusions: Many women with diabetes of reproductive age are poorly prepared for pregnancy, but many are also using less effective contraceptive methods. These areas should be addressed if the poor pregnancy outcome in women with diabetes are to be improved, possibly through the development of an evidenced-based structured education course to target pre-conception and contraception.